Enhancing Digital Literacy through the Role of YouTube in English Phonology Class: Students’ Perception - Fathira, Vina; Masbiran, Gunaldi; Elsara, Wenny (Universitas Lancang Kuning, 2024)
English phonology should be taught properly in online learning. It is difficult since the teacher and students are not in direct contact. The YouTube platform is one method for assisting students in learning and practicing English Phonology in English Phonology lesson. The purpose of this study is to investigate students’ perceptions of improving digital literacy through the use of YouTube in English Phonology class. The research approach was descriptively quantitative. Total sampling was used to get the sample for this study, which consisted of 14 students. The research instrument was a 15-question questionnaire distributed to students using Google form. The data was gathered by asking students to select one of four answers on a Likert scale in the questionnaire. The data was evaluated after it was collected based on the responses of the students in the questionnaire. The findings revealed that the students’ perceptions of improving digital literacy through the function of YouTube in English Phonology class in online learning were satisfied and beneficial. However, just a few students expressed dissatisfaction with using YouTube because the student’ lack of using YouTube in daily life to upload and find the best material to the English Phonology. The conclusion of the research was the students’ perception in the role of YouTube in enhancing digital literacy’ students in English Phonology class was feeling satisfied with the additional access to understand the material and practicing some cases in phonological problem when the material taken from the book was not clear enough to understand.